Innovative and integrated new solutions for sustainable employability project - Matas-Terrón, Antonio; Elósegui-Bandera, Eduardo; Casquero-Arjona, Dolores (My University, 2017)
Innovative and Integrated New Solutions for Sustainable Employability (INTENSE) project aims at improving youth employment in Europe. It is focused on a sub-group so-called NEETs (not in education, employment and training) which is not reached (compare Eurofound 2012, Eurofound 2015) by usual means of employment centred initiatives for educationally deprived youth with psychosocial, mental, multifactorial problems, problematic lifestyles, disabilities, etc. Eurofound 2015, identifies a europe-wide need of this target group to be addressed. They also include the call for the development of holistic approaches in order to achieve sustainability. The above- mentioned need provides the stimulus for the consortium to develop (1st part of the project) and test (2nd part of the project) a client-centered educational concept. In essence, the following 3 dimensions are taken into account: 1st dimension - Compensation. The compensatory aspect concerns the assignment of a Transition Coach who works systemically and enables the clients to recognise their own educational needs, to ask for the coach's support on their own initiative, to develop their own goals and work on the achievement of the latter in an independent manner. 2nd dimension - prevention. The studies which identified the need for a holistic approach, define the requirement of national support systems to act in a preventive manner in order to produce as few NEETs as possible and, if applicable, start the holistic approach at an early stage. 3rd dimension - Structure and Cooperation. The issue going hand in hand with the points mentioned above is the explanation of structural aspects with regards to the success of integrated approaches. By involving the stakeholders at an early stage and throughout the entire project, a solid basis for achieving cross-sectoral cooperation is created. The role of the University of Malaga is to ensure the evaluation of the project development (1st part of the project) and implementation (2nd part of the project) using modern, and scientific methods. For this purpose, the university will apply the Stufflebeam Model during the development phase and evaluates the implementation phase according to effectiveness and efficiency by applying the Contribution Analysis (Mayne 2008).
Keywords: Jóvenes - Trabajo; Sustainable employability; European project